Education and Libraries for Sustainable Development in Nigeria - Princess Lilian Iroka; Chigozie Martin Ndulaka (Archives of Current Research International, 2018)
The paper established a relationship between the library, education and sustainable development. One important resource for achieving the goals and objectives of education is the library. It discussed the library as a requisite for education for sustainable development at all levels of education and professions. It also emphasized the role of libraries in information dissemination to individuals and organizations at all levels. This paper also highlighted the problems militating against the performances of library and educational system and made recommendations. Finally, the paper emphasized the need to reposition and revamp our libraries and the entire educational system in other to make much progress towards sustainable development in Nigeria.